2018
DOI: 10.3389/frobt.2018.00044
|View full text |Cite
|
Sign up to set email alerts
|

A Soft-Inflatable Exosuit for Knee Rehabilitation: Assisting Swing Phase During Walking

Abstract: In this paper, we present a soft-inflatable exosuit to assist knee extension during gait training for stroke rehabilitation. The soft exosuit is designed to provide 25% of the knee moment required during the swing phase of the gait cycle and is integrated with inertial measurement units (IMUs) and smart shoe insole sensors to improve gait phase detection and controller design. The stiffness of the knee joint during level walking is computed using inverse dynamics. The soft-inflatable actuators, with an I cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 29 publications
0
52
2
Order By: Relevance
“…There are about 7.0 million stroke survivals in China and 6.6 million in the United States [109,110]. Stroke is known as the cause of paralysis, loss of motor function, paresis-weakness of muscle, plegia-complete loss of muscle action, and muscle atrophy [34,108,109]. Impaired walking and sit-stand transition are the main reason that poststroke patients cannot live independently [107,108].…”
Section: Knee Neurological Disorders and Its Biomechanicalmentioning
confidence: 99%
See 2 more Smart Citations
“…There are about 7.0 million stroke survivals in China and 6.6 million in the United States [109,110]. Stroke is known as the cause of paralysis, loss of motor function, paresis-weakness of muscle, plegia-complete loss of muscle action, and muscle atrophy [34,108,109]. Impaired walking and sit-stand transition are the main reason that poststroke patients cannot live independently [107,108].…”
Section: Knee Neurological Disorders and Its Biomechanicalmentioning
confidence: 99%
“…Impaired walking and sit-stand transition are the main reason that poststroke patients cannot live independently [107,108]. And about 30% of poststroke patients have difficulty in ambulation without assistance [109]. Some evidences showed that 70% of poststroke patients can recover their walking capabilities by rehabilitation [108,111].…”
Section: Knee Neurological Disorders and Its Biomechanicalmentioning
confidence: 99%
See 1 more Smart Citation
“…This suit uses electric foot switches for the motion detection. Sridar et al [29] developed a soft-inflatable exosuit for knee rehabilitation. This device uses IMUs and shoe insole sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Exosuits actively transmit power to the human body either using cables, moved by electric motors (Figure 2.3.b), or soft pneumatic actuators (Figure 2.3.c), embedded in the garment. The latter paradigm was probably among the first to be proposed [41] and has been explored to assist stroke patients during walking [42], to increase shoulder mobility in subjects with neuromuscular conditions [43], to help elbow movements [44] and for rehabilitation purposes to train and aid grasping [45][46][47].…”
Section: Attaching a Robot To The Human Bodymentioning
confidence: 99%